INOVASI PELAYANAN SOBAT DUKCAPIL DALAM PENERBITAN AKTA KEMATIAN PADA MASA PANDEMIC COVID-19 DI KOTA TANGERANG PROVINSI BANTEN: Innovation of Dukcapil Services in Issuance of Death Certificates During the Covid-19 Pandemic in Tangerang City, Banten Province - Ayu Lestari (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2023)
The Problem the low level of public awareness in managing population documents makes the Tangerang City Population and Civil Registration Office create an online namely SOBAT Dukcapil. The low level of public awareness is due to the fact that the data collection on the number of deaths is less than the number of death certificates issued. Purpose: The purpose of this study was to identify and analyze Dukcapil Service Innovations in Issuing Death Certificates during the COVID-19 Pandemic in Tangerang City, Banten Province. Methods: This study uses a descriptive qualitative method with an inductive approach and an analysis of Rogers' theory of service innovation. Data collection techniques using in-depth interviews (13 informants), documentation and observation. Results/Findings: data collection on the number of issuance of death certificates that are not appropriate, lack of comprehensive socialization, less stable network, lack of Human Resources (HR). Conclusion: the use of these innovations is still relatively low and rarely used by the public, and is still not innovative enough when analyzed using existing theories, there are three characteristics, each of which has problems. The inhibiting factor is the data collection on the number of issuance of death certificates that are not appropriate. Efforts have been made to hold coordination meetings with the RT and RW heads, conduct a thorough socialization, cooperate with Telkom related to the network, add human resources from CPNS employees.